A Competitive Advantage of Middle-Sized Diatoms From Increasing Seawater CO2 - Zhang, Qi; Luo, Ya-Wei (Frontiers in Microbiology, 2022)
Diatoms, one of the most important phytoplankton groups, fulfill their carbon demand from seawater mainly by obtaining passively diffused carbon dioxide (CO2) and/or actively consuming intracellular energy to acquire bicarbonate (HCO3-). An anthropogenically induced increase in seawater CO2 reduces the HCO3- requirement of diatoms, potentially saving intracellular energy and benefitting their growth. This effect is commonly speculated to be most remarkable in larger diatoms that are subject to a stronger limitation of CO2 supply because of their smaller surface-to-volume ratios. However, we constructed a theoretical model for diatoms and revealed a unimodal relationship between the simulated growth rate response (GRR, the ratio of growth rates under elevated and ambient CO2) and cell size, with the GRR peaking at a cell diameter of ~7 μm. The simulated GRR of the smallest diatoms was low because the CO2 supply was nearly sufficient at the ambient level, while the decline of GRR from a cell diameter of 7 μm was simulated because the contribution of seawater CO2 to the total carbon demand greatly decreased and diatoms became less sensitive to CO2 increase. A collection of historical data in CO2 enrichment experiments of diatoms also showed a roughly unimodal relationship between maximal GRR and cell size. Our model further revealed that the “optimal” cell size corresponding to peak GRR enlarged with the magnitude of CO2 increase but diminished with elevating cellular carbon demand, leading to projection of the smallest optimal cell size in the equatorial Pacific upwelling zone. Last, we need to emphasize that the size-dependent effects of increasing CO2 on diatoms are multifaceted, while our model only considers the inorganic carbon supply from seawater and optimal allocation of intracellular energy. Our study proposes a competitive advantage of middle-sized diatoms and can be useful in projecting changes in the diatom community in the future acidified high-CO2 ocean.